Investigating the antidepressant effect of Ziyan green tea on chronic unpredictable mild stress mice through fecal metabolomics - Jia, Wenbao; Tang, Qian; Zou, Yao; Yang, Yang; Wu, Wenliang; Xu, Wei (Frontiers in Microbiology, 2023)
Introduction Some studies have shown the effectiveness of tea in reducing depression. Gut flora dysfunction is strongly associated with depression. The mechanism by which Ziyan green tea ameliorates depression is not clear. Methods In this study, we examined the impact of Ziyan green tea on mice exhibiting symptoms similar to depression. We specifically focused on the role of intestinal flora and its metabolites. We first established a chronic unpredictable mild stress (CUMS) mouse model to induce depressive symptoms and conducted behavioural tests, biochemical tests, and pathological tissue analysis. We also investigated gut microbiota changes by 16S rRNA sequencing and measured faecal metabolites in mice using UHPLC-MS/MS. Results The results showed that Ziyan green tea intervention improved depression-like behaviour, neurobiochemical factors, and reduced levels of pro-inflammatory factors in CUMS mice. Spearman’s correlation analysis showed that different microbial communities (Corynebacterium, Faecalibaculum, Enterorhabdus, Desulfovibrio) correlation with differential metabolites (Cholic acid, Deoxycholic acid, etc.) and depression-related biochemical indicators (5-HT, DA, BDNF, IL-6, and TNF-α). Discussion In conclusion, our findings suggest that both low and high-dose interventions of Ziyan green tea have positive preventive effects on CUMS mice without dose dependence, partly because they mainly affect intestinal Purine Metabolism, Bile Acid Biosynthesis and Cysteine Metabolism in CUMS mice, thus stimulating brain 5-HT, DA and BDNF, and decreasing the inflammatory factors IL-6, TNF-α, activate the composition of intestinal flora, improve the intestinal flora environment and thus promote the production of intestinal metabolites, which can be used for depression treatment. It is suggested that Ziyan green tea may achieve an antidepressant effect through the gut-microbiota-brain axis.